Hyperspectral venous image quality assessment for optimum illumination range selection based on skin tone characteristics - Shahzad, A. (BioMed Central Ltd., 2014)
Background: Subcutaneous veins localization is usually performed manually by medical staff to find suitable vein to insert catheter for medication delivery or blood sample function. The rule of thumb is to find large and straight enough vein for the medication to flow inside of the selected blood vessel without any obstruction. The problem of peripheral difficult venous access arises when patient's veins are not visible due to any reason like dark skin tone, presence of hair, high body fat or dehydrated condition, etc.Methods: To enhance the visibility of veins, near infrared imaging systems is used to assist medical staff in veins localization process. Optimum illumination is crucial to obtain a better image contrast and quality, taking into consideration the limited power and space on portable imaging systems. In this work a hyperspectral image quality assessment is done to get the optimum range of illumination for venous imaging system. A database of hyperspectral images from 80 subjects has been created and subjects were divided in to four different classes on the basis of their skin tone. In this paper the results of hyper spectral image analyses are presented in function of the skin tone of patients. For each patient, four mean images were constructed by taking mean with a spectral span of 50Â nm within near infrared range, i.e. 750-950Â nm. Statistical quality measures were used to analyse these images.Conclusion: It is concluded that the wavelength range of 800 to 850Â nm serve as the optimum illumination range to get best near infrared venous image quality for each type of skin tone. Â© 2014 Shahzad et al; licensee BioMed Central Ltd.